'Against the privatised, the preconditioned, and the asylum-like': Frank van Klingeren's challenge to open architecture. Issue 2 (3rd April 2022) - Sarıçayır, Ecem
Abstract : This paper traces the history of two community centres, De Meerpaal (1965–1967) and Het Karregat (1973), designed by the Dutch architect Frank van Klingeren. After situating his work within the historical context of the 1960s and 1970s architectural developments in the Netherlands, Van Klingeren's architectural practice as demonstrated through his community centres is analysed through the conceptual framework of 'open architecture' proposed by Esra Akcan. Although they received praise from national and international commentators alike, Van Klingeren's open community centres also met resistance from government officials and journalists, as well as users of the buildings. The focus of investigation is on Van Klingeren's struggle against the planned renovation of De Meerpaal and his decision to file an injunction claiming his right of authorship over the building in a final attempt to safeguard the building's openness. This paper draws attention to the contradictions of Van Klingeren's open architecture and argues that his attempt to protect De Meerpaal through court action is indicative of the limitations of his open architectural practice. In doing so, this paper explores the question of architectural authorship in discussions on open architecture.